Understanding the effects of organic versus conventional farming on soil organic carbon characteristics – a chronosequence study - Koorneef, Guusje J.; Pulleman, Mirjam Margreet; de Goede, Ron G.M.; Barré, Pierre; Baudin, François; van Rijssel, Sophie Q.; Comans, Rob N.J. (Elsevier, 2025)
Organic farming aims at producing high quality, nutritious food while sustaining the health of soils and ecosystems, for which it relies on ecological processes. The amount and quality of soil organic carbon (SOC) influence many soil ecological processes that underlie ecosystem services. However, the effect of organic farming on the amount and especially the quality of SOC is not yet clear. We therefore investigated the long-term influence of organic arable farming on SOC characteristics in topsoil (0–15 cm).